The Influence of Perceived Organizational Support and Work Life Balance on Work Engagement (Case Study at PL PLN (Persero) UPT Karawang) - Rosdianto, Fajar; Dudija, Nidya (International Journal of Science, Technology & Management, 2025)
PLN UPT Karawang is responsible for managing electricity transmission assets across the regions of Karawang, Bekasi, Purwakarta, and Subang, with a total capacity of 6,530 MVA from 60 transformer units, serving 17 high-voltage consumers. By the end of 2024, this unit had fulfilled only 95.14% of its workforce requirements, which may lead to excessive workloads, reduced work-life balance, and increased risks of fatigue and declining employee well-being. Furthermore, a drop in the work engagement index from 89.74% in 2022 to 88.89% in 2023, along with suboptimal achievements in the Work Condition and Recognition dimensions, reflects potential weaknesses in organizational support and recognition for employees. This decline indicates a weakening in leadership quality, supervision, and organizational culture, which can negatively affect employee motivation, job satisfaction, and loyalty. Additionally, a reduced sense of meaningfulness in work and worsening working conditions may lower productivity and increase stress levels.This study aims to analyze the influence of direct supervisor support and work-life balance on employee work engagement at PLN UPT Karawang. Data were collected through a questionnaire using a 1–5 scale and analyzed using the Partial Least Squares method within the Structural Equation Modeling framework. The results indicate that both organizational support and work-life balance have a significant influence, both partially and simultaneously, on work engagement. The coefficient of determination value of 0.406 suggests that 40.6% of work engagement is explained by these two variables, while the remaining 59.4% is influenced by other factors. This study is limited by the scope of respondents and variables, so future research is recommended to broaden the population and include other variables such as leadership, organizational culture, and psychological well-being to gain a deeper understanding.